ChemInform Abstract: The Regioselective Iodination of Quinolines, Quinolones, Pyridones, Pyridines and Uracil. Issue 17 (April 2016) - Dutta, Uttam; Deb, Arghya; Lupton, David W.; Maiti, Debabrata
Abstract: The title iodination is a radical based direct C—H iodination, which occurs at C3 or/and C5 position depending on the substrates.